2016
DOI: 10.1021/acsami.5b09963
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Delaminated Organotalc: The Use of Polyamidoamine Dendrons

Abstract: A sequence of generations of the polyamideamine dendron, PAMAM-talc-Gn (n = 1-7), was constructed on the surfaces of ethylenediaminepropyl-functionalized magnesium phyllosilicate lamellas by using a modified microwave-assisted synthesis. The successful functionalization of the inorganic layers by the organic dendrimer was confirmed by FTIR and (13)C NMR spectroscopies, elemental analyses, and thermogravimetric analysis (TGA). The solid materials presented an increase in their interlamellar space and disorganiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 59 publications
(142 reference statements)
0
23
0
Order By: Relevance
“…showed that the delamination of organotalc could be achieved by a simple ultrasound treatment in water by creation of surface groups on lamella. Recently, Andrade et al . reported an increase up to 54 Å of the organotalc interlayer space by functionalization of the layers with dendrimers.…”
Section: Talc‐like Structuresmentioning
confidence: 99%
“…showed that the delamination of organotalc could be achieved by a simple ultrasound treatment in water by creation of surface groups on lamella. Recently, Andrade et al . reported an increase up to 54 Å of the organotalc interlayer space by functionalization of the layers with dendrimers.…”
Section: Talc‐like Structuresmentioning
confidence: 99%
“…The synthesis of the organotalcs were reported in our previous work [25]. Briefly, the first generation (PAMAM-talc-G1) was synthesized by mixing 1.0 g EDA-talc (as reported by Moura et al [11]), 4.0 mL methanol and 1.0 mL MA in an 80 mL all-polymer autoclave lined with Teflon ® and heated under microwave irradiation, at 40 W for 40 min.…”
Section: Synthesis Of Pamam Modified-organotalcmentioning
confidence: 99%
“…When looking at the rate constants of the adducts (k 2 ) in Table 1, a tenfold increase in reaction rate can be seen in the higher generation dendron organotalcs (k 2 ¼ 0.42 g mol À1 h À1 in PAMAM-talc-G7) than the lower generation dendron organotalcs (k 2 ¼ 0.04 g mol À1 h À1 in PAMAM-talc-G1). In the higher dendron generations, the reaction is faster because a large amount of basic sites in the surface of the dendrons is available to interact with iodine [25], which interact, firstly, with the basic sites from the surface and then slowly diffuse to the core. There is a small difference between the reaction rate with PAMAMtalc-G5 and PAMAM-talc-G7.…”
Section: Iodine Interaction In Pamam-organotalcmentioning
confidence: 99%
See 2 more Smart Citations